KINERJA PEGAWAI DAN FAKTOR YANG MEMPENGARUHINYA: Studi Kasus di STAIN Pekalongan - Zaenal Mustakim (JURNAL PENELITIAN, 2014)
The success of an institution is influenced by the level of employee performance. This study identified two main issues: (1) employee performance at STAIN Pekalongan based on tenure, age, and gender; and (2) the factors influencing employee performance. The results show that, first, based on tenure, employees with more than 10 years of service demonstrate average performance (mean score 3.95 or 79%); those with tenure ≥5 and <10 years also show average performance (mean score 4.00 or 80%); while employees with less than 5 years of service demonstrate high performance (mean score 4.04 or 81%). Based on age, employees over 35 years old show average performance (mean score 3.96 or 79.2%), whereas those under 35 years old demonstrate high performance (mean score 4.03 or 81%). Based on gender, male employees demonstrate high performance (mean score 4.06 or 81.22%), while female employees show average performance (mean score 3.95 or 79.08%). Second, the factors influencing employee performance include a clean and well-organized workspace, job training, implementation of a fingerprint attendance system, salary increases, rewards for job performance, and changes in leadership.